Global Taxonomy and Phylogeny of Irpicaceae (Polyporales, Basidiomycota) With Descriptions of Seven New Species and Proposals of Two New Combinations - Li, Yue; He, Shuang-Hui; Chen, Che-Chih; Nakasone, Karen K.; Ma, Hai-Xia (Frontiers in Microbiology, 2022)
The phylogenetic analyses of the family Irpicaceae were carried out based on a complete global sampling. The dataset that included concatenated ITS1-5.8S-ITS2 and nrLSU sequences of 67 taxa of Irpicaceae from around the world were subjected to the Maximum likelihood analyses and Bayesian inference. In the phylogenetic tree, species from 14 genera were distributed in 9 clades, among which five genera — Irpex, Phanerochaetella, Byssomerulius, Cytidiella, and Meruliopsis received high support values. The genus Efibula was shown to be paraphyletic and four subclades could be recognized, while Phanerochaete allantospora, Leptoporus mollis and several species from Ceriporia and Candelabrochaete formed a large clade with relatively strong support. Based on the molecular and morphological evidence, seven new corticioid species — Candelabrochaete guangdongensis, Efibula grandinosa, E. hainanensis, E. shenghuae, E. taiwanensis, Irpex alboflavescens and Phanerochaetella sinensis were revealed from the materials mostly from East Asia. The monotypic genus Flavodontia, newly described from southwestern China, is regarded as a later synonym of Irpex, and the new combination I. rosea is proposed. In addition, Phanerochaetella queletii is proposed for a taxon first described from Italy and newly recorded from China; Phanerochaete jose-ferreirae from Portugal is determined to be a later synonym. Descriptions and illustrations of the new species and the newly combined taxa are presented, and morphological comparasions for the known species of Efibula and Phanerochaetella are provided.